From Rule-Based Sharaf to Meaning-Oriented Morphology: A Systematic Literature Review of Arabic Morphology Instruction (2010–2025) - MUHAMMAD TAMPUBOLON (PPPBA, 2025)
Traditional sharaf (Arabic morphology) instruction has predominantly relied on rule-based morphology instruction, emphasizing the memorization of derivational patterns (wazn) and grammatical rules with minimal attention to form–meaning mapping. Although effective for promoting formal accuracy, this approach has been increasingly criticized for its limited contribution to functional morphological competence and communicative language use in Arabic as a second or foreign language (ASL/AFL) context. This study employs a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework to synthesize contemporary empirical and theoretical research on Arabic morphology instruction. Peer-reviewed studies published between 2010 and 2025 were retrieved from Scopus, Web of Science, and DOAJ and analyzed using thematic synthesis and pedagogical paradigm mapping. The findings indicate a substantial paradigm shift from rule-based morphology teaching toward meaning-oriented morphology instruction, including semantic-based morphology, contextualized morphology teaching, lexical-morphological approaches, and usage-based morphology pedagogy. These approaches consistently demonstrate positive effects on learners’ morphological awareness, vocabulary acquisition, reading comprehension, and overall second language proficiency, outperforming purely form-focused instructional models. The study highlights the necessity of reconceptualizing Arabic morphology pedagogy by integrating cognitive linguistics, usage-based learning, and communicative language teaching principles. Such integration is crucial for enhancing the pedagogical relevance of sharaf instruction and aligning Arabic language education with contemporary second language acquisition (SLA) research.